2008
DOI: 10.1016/j.jsbmb.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Lithocholic acid down-regulation of NF-κB activity through vitamin D receptor in colonic cancer cells

Abstract: Lithocholic acid (LCA), a secondary bile acid, is a vitamin D receptor (VDR) ligand. 1,25-Dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), the hormonal form of vitamin D, is involved in the antiinflammatory action through VDR. Therefore, we hypothesize that LCA acts like 1,25(OH) 2 D 3 to drive anti-inflammatory signals. In present study, we used human colonic cancer cells to assess the role of LCA in regulation of the pro-inflammatory NF-κB pathway. We found that LCA treatment increased VDR levels, mimicking the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Additionally, work by Froicu et al (2006) showed that VDR is required to control gastrointestinal inflammation in Il10 knockout mice, as Il10/Vdr double knockout mice develop exacerbated IBD symptoms associated with high local expression of IL2, IFN-g, IL1b, TNF-a and IL12. In line with this, 1,25(OH) 2 D 3 was shown to antagonize the NF-kB pathway and the production of IL8 in CRC cells treated with IL1b (Sun et al 2008). These results suggest that 1,25(OH) 2 D 3 / VDR signalling has a potent anti-inflammatory action in vitro and in vivo that may influence the colonic inflammatory scenario that pre-dispose to the development of CRC.…”
Section: Angiogenesissupporting
confidence: 70%
“…Additionally, work by Froicu et al (2006) showed that VDR is required to control gastrointestinal inflammation in Il10 knockout mice, as Il10/Vdr double knockout mice develop exacerbated IBD symptoms associated with high local expression of IL2, IFN-g, IL1b, TNF-a and IL12. In line with this, 1,25(OH) 2 D 3 was shown to antagonize the NF-kB pathway and the production of IL8 in CRC cells treated with IL1b (Sun et al 2008). These results suggest that 1,25(OH) 2 D 3 / VDR signalling has a potent anti-inflammatory action in vitro and in vivo that may influence the colonic inflammatory scenario that pre-dispose to the development of CRC.…”
Section: Angiogenesissupporting
confidence: 70%
“…It suppresses activation of the p65 subunit of the NF-kB complex in colon cancer cells, thereby preventing binding of NF-kB to DNA (33,34). Calcitriol also increases the expression of the inhibitor of NF-kB, IkB (32,33,35). These effects of calcitriol on NF-kB have also been shown in a mouse model of colon cancer where an increase in dietary vitamin D resulted in a 4.5-fold decrease in NFkB activation in colonic epithelial cells (36).…”
Section: Cancer Epidemiol Biomarkers Prev; 24(12) December 2015mentioning
confidence: 76%
“…It suppresses activation of the p65 subunit of the NF-kB complex in colon cancer cells, thereby preventing binding of NF-kB to DNA (33,34). Calcitriol also increases the expression of the inhibitor of NF-kB, IkB (32,33,35).…”
Section: Cancer Epidemiol Biomarkers Prev; 24(12) December 2015mentioning
confidence: 99%
“…Mouse epithelial cells were lysed in lysis buffer (1% Triton X-100, 150 mM NaCl, 10 mM Tris pH 7.4, 1 mM EDTA, 1 mM EGTA pH 8.0, 0.2 mM sodium orthovanadate, and protease inhibitor cocktail). Immunoblot was performed with the following primary antibodies and visualized by enhanced chemiluminescence (43)(44): anti-␤-catenin (BD, Transduction Laboratories), anti-villin, antiFrizzled 7 (Santa Cruz Biotechnology, Santa Cruz, CA), anti-GSK-3␤ (BD), anti-phosphor-GSK-3␤ (Ser9), anti-phospho-␤-catenin (Ser552), anti-phospho-␤-catenin (Ser33, 37, Thr41) and phosphor-Akt (T308) (Cell Signal, Beverly, MA), or anti-␤-actin (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%